Rancang Bangun Virtual Tour Sebagai Media Pengenalan Sekolah Berbasis Web - Baswardono, Wiyoga; Fakry, Hafidzh (Institut Teknologi Garut, 2025)
SMP 1 Sukawening, located in Sukawening, West Java, is a junior high school (SMP) committed to providing quality education and equipping students with practical skills. However, the school still uses banners as a method of introduction, which are less effective in displaying attractive visuals. Therefore, this study proposes a web-based virtual tour to introduce the school environment interactively. This technology provides an innovative way for prospective students to explore the school environment thoroughly without the need for a physical visit. The purpose of this research is to implement a web-based Virtual Tour. To implement the Web-based School Introduction Virtual Tour, the Multimedia Development Life Cycle (MDLC) method with six stages is used, namely: concept, design, material collection, creation, testing, and distribution. It is hoped that this research will bring innovation in school introductions that are more interesting, effective, and easily accessible, so that prospective students and parents can obtain more comprehensive information about the school without having to visit physically.